Hubungan pengelolaan waktu dengan prokrastinasi akademik pada mahasiswa - Maulana, Muhammad Dimas (Maliki Interdisciplinary Journal, 2026)
Academic procrastination is the behavior of postponing the completion of academic tasks that often occurs in students and has a negative impact on academic achievement, mental health, and psychological well-being. One important factor influencing academic procrastination is time management skills. This study aims to examine the relationship between time management and academic procrastination in students. The research approach used a quantitative correlational method involving 120 active students as respondents. The instruments used were a time management scale and an academic procrastination scale. The results showed a significant negative relationship between time management and academic procrastination. The better a student's time management skills, the lower their level of academic procrastination. This finding emphasizes the importance of strengthening time management skills as an effective strategy in reducing academic procrastination among students.